PENERAPAN MODEL PEMBELAJARAN LEARNING CYCLE 7E UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA - Partini Partini; Budijanto Budijanto; Syamsul Bachri (Graduate School of Universitas Negeri Malang, 2017)
This study aims to improve students' critical thinking skills through learning cycle 7E learning model on geography subjects. This study uses classroom action research design. This research was conducted in the SMA. The subject of the research is students of class X which consist of 14 students. The implementation of the cycles is done through four phases: planning, acting, observing and reflecting. The data used in the study are the result of observation and students’ test scores. Data are analyzed by simple statistics namely percentage. The results shows that the critical thinking ability of students in the first cycle is 69.92%, while in the second cyclethe percentage then increases to 76.71%, so there is a 7.71% increase between the first cycle and the second cycle.Penelitian ini bertujuan untuk meningkatkan kemampuan berpikir kritis siswa melalui model pembelajaran learning cycle 7E mata pelajaran Geografi. Penelitian ini menggunakan rancangan penelitian tindakan kelas. Penelitian ini dilaksanakan di SMA. Subjek penelitian siswa kelas X yang berjumlah 14 siswa. Pelaksanaan siklus melalui 4 tahap, yaitu perencanaan, pelaksanaan tindakan, pengamatan, dan refleksi. Data yang digunakan dalam penelitian adalah hasil observasi dan nilai tes siswa, data dianalisis dengan statistika sederhana, yaitu persentase. Hasil penelitian menunjukkan bahwa kemampuan berpikir kritis siswa pada siklus I sebesar 69,92%, sedangkan pada siklus II meningkat menjadi 76,71%, sehingga ada peningkatan sebesar 7,71% antar siklus I dengan siklus II.